A Host ER Fusogen Is Recruited by Turnip Mosaic Virus for Maturation of Viral Replication Vesicles. Issue 2 (11th December 2018) - Movahed, Nooshin; Sun, Jiaqi; Vali, Hojatollah; Laliberté, Jean-François; Zheng, Huanquan
Abstract : Interacting with 6K2 of TuMV ER fusogen RHD3 is recruited by TuMV for the efficient formation of replication-competent vesicles in infected host cells. Abstract: Like other positive-strand RNA viruses, the Turnip mosaic virus (TuMV) infection leads to the formation of viral vesicles at the endoplasmic reticulum (ER). Once released from the ER, the viral vesicles mature intracellularly and then move intercellularly. While it is known that the membrane-associated viral protein 6K2 plays a role in the process, the contribution of host proteins has been poorly defined. In this article, we show that 6K2 interacts with RHD3, an ER fusogen required for efficient ER fusion. When RHD3 is mutated, a delay in the development of TuMV infection is observed. We found that the replication of TuMV and the cell-to-cell movement of its replication vesicles are impaired in rhd3 . This defect can be tracked to a delayed maturation of the viral vesicles from the replication incompetent to the competent state. Furthermore, 6K2 can relocate RHD3 from the ER to viral vesicles. However, a Golgi-localized mutated 6K2 GV is unable to interact and relocate RHD3 to viral vesicles. We conclude that the maturation of TuMV replication vesicles requires RHD3 for efficient viral replication and movement.